2023
DOI: 10.1186/s40659-023-00459-w
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells (hUC-MSCs) alleviate paclitaxel-induced spermatogenesis defects and maintain male fertility

Abstract: Chemotherapeutic drugs can cause reproductive damage by affecting sperm quality and other aspects of male fertility. Stem cells are thought to alleviate the damage caused by chemotherapy drugs and to play roles in reproductive protection and treatment. This study aimed to explore the effects of human umbilical cord mesenchymal stem cells (hUC-MSCs) on alleviating paclitaxel (PTX)-induced spermatogenesis and male fertility defects. An in vivo PTX-induced mice model was constructed to evaluate the reproductive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Chemotherapeutic drugs can cause reproductive damage due to their gonadotoxic effects on sperm quality and other aspects of male fertility. The study by Zhang Y et al focuses on showing how stem cells can reportedly alleviate the damage caused by chemotherapy drugs and to play roles in reproductive protection and treatment [115]; this was conducted in order to investigate whether exosomes derived from human umbilical cord mesenchymal stem cells (hucMSC-derived exosomes) can repair injured endometrial epithelial cells (EECs) and reduce their death, and exhibit an anti-inflammatory effect against OGD/R (oxygen and glucose deprivation/reoxygenation) [116]. As reported in 2016 by multiple groups, scientists developed the ability to culture human embryos for 12 or 13 days [117], and in light of such developments, ethicists have called for the policy to be reconsidered, with some even suggesting that research should be allowed until the 21st or 28th day after fertilization [118].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs can cause reproductive damage due to their gonadotoxic effects on sperm quality and other aspects of male fertility. The study by Zhang Y et al focuses on showing how stem cells can reportedly alleviate the damage caused by chemotherapy drugs and to play roles in reproductive protection and treatment [115]; this was conducted in order to investigate whether exosomes derived from human umbilical cord mesenchymal stem cells (hucMSC-derived exosomes) can repair injured endometrial epithelial cells (EECs) and reduce their death, and exhibit an anti-inflammatory effect against OGD/R (oxygen and glucose deprivation/reoxygenation) [116]. As reported in 2016 by multiple groups, scientists developed the ability to culture human embryos for 12 or 13 days [117], and in light of such developments, ethicists have called for the policy to be reconsidered, with some even suggesting that research should be allowed until the 21st or 28th day after fertilization [118].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs can cause reproductive damage due its gonadotoxyc effects on sperm quality and other aspects of male fertility. Zhang Y et al focus their study showing how stem cells are thought to alleviate the damage caused by chemotherapy drugs and to play roles in reproductive protection and treatment [98], in order to investigate whether exosomes derived from human umbilical cord mesenchymal stem cells (hucMSC-derived exosomes) can repair injured endometrial epithelial cells (EECs) and reduce their death, and exhibit an anti-inflammatory effect against OGD/R (oxygen and glucose deprivation/reoxygenation) [99]. As reported in 2016 by multiple groups, scientists developed the ability to culture human embryos for 12 or 13 days [100], ethicists have also called for the policy to be revisited, and some have suggested that research should be allowed until the 21 st or 28 th day after fertilization [101].…”
Section: Discussionmentioning
confidence: 99%